2021
DOI: 10.1155/2021/5587188
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Model to Predict the Disease Severity and Outcome in COVID-19 Patients

Abstract: The novel coronavirus (COVID-19) outbreak produced devastating effects on the global economy and the health of entire communities. Although the COVID-19 survival rate is high, the number of severe cases that result in death is increasing daily. A timely prediction of at-risk patients of COVID-19 with precautionary measures is expected to increase the survival rate of patients and reduce the fatality rate. This research provides a prediction method for the early identification of COVID-19 patient’s outcome base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…The proposed pipeline achieves a classification accuracy of 99.65% using support vector classifier [ 30 ] 2020 Transfer learning Convolutional neural networks VGG16, ResNet50, Inception v3 In this study, the transfer learning technique has been applied to clinical images. Texture feature extraction is accomplished using Haralick features which focus only to detect COVID-19 using statistical analyses [ 31 ] 2021 Supervised learning Classification Random Forest, Logistic Regression, Extreme Gradient Boosting Out of all the three methods, Random Forest gave more accuracy of 0.952. But, due to insufficient dataset, data imbalance occurs in this proposed approach.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed pipeline achieves a classification accuracy of 99.65% using support vector classifier [ 30 ] 2020 Transfer learning Convolutional neural networks VGG16, ResNet50, Inception v3 In this study, the transfer learning technique has been applied to clinical images. Texture feature extraction is accomplished using Haralick features which focus only to detect COVID-19 using statistical analyses [ 31 ] 2021 Supervised learning Classification Random Forest, Logistic Regression, Extreme Gradient Boosting Out of all the three methods, Random Forest gave more accuracy of 0.952. But, due to insufficient dataset, data imbalance occurs in this proposed approach.…”
Section: Discussionmentioning
confidence: 99%
“…Before analyzing, they partitioned data using 10 k-cross validation and fixed data imbalance using synthetic minority over-sampling technique (SMOTE). They concluded that RF performed better than the other two algorithms [22].…”
Section: Related Workmentioning
confidence: 99%
“…Prathyusha K. [4] et.al applied various machine learning regression algorithms like linear regressor, polynomial regressor and achieved the best results with the polynomial regression technique. A. Lakshmanarao [5] et.al applied various regression techniques for analyzing and predicting corona disease and achieved good results with linear regression. Sumayh S. Aljameel [6] et.al applied three classification algorithms random forest, Gradient Boosting, and Logistic Regression.…”
Section: Literature Reviewmentioning
confidence: 99%